The Austerity state, "social junk" and the mystification of violence - Grover, Chris (Demystifying power, crime and social harm, 2023)
This chapter draws upon and extends Box’s (1983) Power, Crime and Mystification to focus upon the harms that enduring austerity is producing in Britain. Examining how enduring social security austerity affects working-age ‘social junk’, the chapter argues that the austerity affecting such people has been driven by capitalist social relations and imperatives, in particular the demand that ‘social junk’ (re-)commodifies its labour power. This process, the chapter argues, is embedded in social violence, a form of violence which has a detrimental impact upon lives and life chances, on what Galtung (1969) (Journal of Peace Research 6:167-191) describes as the ‘realisations’ of people, in ways that are both known and alterable. Nevertheless, through state indifference, austerity is left in situ to maim and kill. In doing so, the potential for labour power to be commodified is reduced, reflecting, the chapter argues, the contradictory position of ‘social junk’ in capitalist societies. It is required to maintain downward pressure on wages as part of the reserve army of labour, but it is also constructed as an economic drain upon the fundamental capitalist aim of ever-greater levels of capital accumulation.